Sexual Harassment and Its Impact on Psycho-Cognitive Well-being of Female Undergraduates in a University in Southeastern Nigeria - Ifeoma, Anierobi Elizabeth; Emmanuella, Abbas Comfort; Chukwuemeka, Onyebuchi Albert; Ahuruezenma, Apiti Anthony (MultiTech Publisher, 2024)
This study determined the prevalence, factors, and strategies for intervention for sexual harassment and its impact on the psycho-cognitive well-being of female undergraduates in government universities in Anambra State. This study adopted a Descriptive research design and guided by five research questions. The study sample comprised 442 female undergraduate students drawn using a convenient random technique. A structured questionnaire by the researchers was used for data collection. Face and content validity of the instrument was done by experts in the field of Education. The instrument's reliability was determined using Cronbach Alpha and an alpha coefficient of 0.70 was obtained. The data collected were analysed using Percentages, Mean, and Standard deviation. The findings of this study revealed that sexual harassment is prevalent against female undergraduate students in government universities in Anambra State. It also showed that indecent dressing and immorality among others are contributing factors sustaining the upsurge of sexual harassment against female students. Furthermore, the findings revealed that sexual harassment has a negative impact on both the psychological and cognitive well-being of female students. Finally, it showed that making policies and ensuring prompt implementations among others are strategies for curbing sexual harassment.